5(w+2)=4(w+1)

Simple and best practice solution for 5(w+2)=4(w+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(w+2)=4(w+1) equation:


Simplifying
5(w + 2) = 4(w + 1)

Reorder the terms:
5(2 + w) = 4(w + 1)
(2 * 5 + w * 5) = 4(w + 1)
(10 + 5w) = 4(w + 1)

Reorder the terms:
10 + 5w = 4(1 + w)
10 + 5w = (1 * 4 + w * 4)
10 + 5w = (4 + 4w)

Solving
10 + 5w = 4 + 4w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-4w' to each side of the equation.
10 + 5w + -4w = 4 + 4w + -4w

Combine like terms: 5w + -4w = 1w
10 + 1w = 4 + 4w + -4w

Combine like terms: 4w + -4w = 0
10 + 1w = 4 + 0
10 + 1w = 4

Add '-10' to each side of the equation.
10 + -10 + 1w = 4 + -10

Combine like terms: 10 + -10 = 0
0 + 1w = 4 + -10
1w = 4 + -10

Combine like terms: 4 + -10 = -6
1w = -6

Divide each side by '1'.
w = -6

Simplifying
w = -6

See similar equations:

| 13x+167=180 | | 6x-5x+4=-6 | | w=3(x+y+z)y | | v-16=-6 | | 3c-36=-3c-12 | | 9y-5y+10=-19 | | 0.33-4=-8 | | 2=5w+12 | | 5s-21=39 | | m=6(p+q)q | | 3(x+2)=-5-2(x-4) | | 25-39=11 | | 6X+19X-7=5(5X+5) | | -0.75=-0.6+s | | -2.4x=-2.88 | | 5x+28(x-2)=406 | | x-5x=7x-9x-x | | X+0.375=-1.75 | | -328=-56b+7 | | -5+4r=-5r+4r | | 19-13p=-5-17p | | 0.5+0.5j=0 | | ln(5X+1)=4.5 | | 3x+12=7x-22 | | x+3(x-3)=91 | | 2x=-16+4y | | 3x-66=9x | | 1+k=3k-1 | | -0.6+y=-0.33 | | -28=v-18 | | 20+18x-2=21x | | X-9.2=-4.55 |

Equations solver categories